Application of a stand-alone RTI measuring system with an integrated camera in cultural heritage digitisation - Wilk, Ł.; Lech, P.; Klebowski, M.; Beldyga, M.; Ostrowski, W. (Journal of archaeological science, reports, 2024)
•Construction of standalone RTI imaging solution based on a Raspberry Pi minicomputer.•Qualitative and quantitative comparison of RTI imaging dome with embedded and external camera.•Resolving power and colorimetric evaluation of industrial-grade and high-end camera system.•Evaluation of data acquisition system with various light configurations for ancient pottery artifacts. The Multi-Light Image Collection (MLIC) data, in most cases processed with the Reflectance Transformation Imaging (RTI) technique, is one of the popular methods of documentation and digital representation of movable finds from an archaeological excavation. The manual (hand-held) approach to collecting this data is technically simple and still popular in the case of archaeology. However, an extensive amount of work during image collection is a strong motivation for building RTI acquisition systems, which are also popular, in most cases, in the shape of domes. The research presented in the article focuses on two aspects of building such a device. First, the study examines the effect of the placement and number of lights on the resulting RTI model for a system based on LED stripe-shaped circuits. Secondly, the camera component was studied. Recent development in the area of low-cost accessories for microcomputers resulted in a few new industrial-grade USB cameras with the possibility to take high-resolution images. Cameras designed for use with microcomputers offer broad control of the focus or exposition parameters and provide the possibility to build RTI domes with the fully integrated camera, therefore, almost complete automatization of the capturing and processing of MLIC data. This paper presents the main assumptions and elements of the dome-shaped measurement system, which enables automatic RTI data acquisition and processing together with the evaluation of light configuration used to build relightable models. Amphoras handles with stamps and ancient pottery were used as an objects to evaluate the quality of the relightable models generated from the images acquired by a programmable miniature Arducam camera. Results of comparison with professional high-quality mirrorless cameras show that the quality of images from miniature cameras can be satisfactory for some archaeological objects.